2020
DOI: 10.1007/s00792-020-01206-9
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pH on the activity of ice-binding protein from Marinomonas primoryensis

Abstract: The ability of an ice-binding protein (IBP) from Marinomonas primoryensis (MpIBP) to influence ice crystal growth and structure in non-physiological pH environments was investigated in this work. The ability for MpIBP to retain ice interactivity under stressed environmental conditions was determined via (1) a modified splat assay to determine ice recrystallization inhibition (IRI) of polycrystalline ice and (2) nanoliter osmometry to evaluate the ability of MpIBP to dynamically shape the morphology of a single… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 83 publications
0
8
0
Order By: Relevance
“…However, pH and by extension p K a influence a wide range of research areas include graphene oxide adsorption capacity, 1 peptide self- and co-assembly, 2 and protein structure; 3 even extremophile bacterial ice-binding proteins are hindered at slightly below physiological pH (<6). 4 …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, pH and by extension p K a influence a wide range of research areas include graphene oxide adsorption capacity, 1 peptide self- and co-assembly, 2 and protein structure; 3 even extremophile bacterial ice-binding proteins are hindered at slightly below physiological pH (<6). 4 …”
mentioning
confidence: 99%
“…However, pH and by extension pK a influence a wide range of research areas include graphene oxide adsorption capacity, 1 peptide self-and co-assembly, 2 and protein structure; 3 even extremophile bacterial ice-binding proteins are hindered at slightly below physiological pH (<6). 4 Herein, we describe a method of performing constant pH molecular dynamics (CpHMD) with dynamic stochastic charge neutralization on the basis of the method developed by Radak et al 5 Modifications have been introduced to enable net charge neutralization as well as for the capture of broad apparent pK a shifts in aggregates of minimal low dielectric constants. In the validation of this methodology as well as the exploration of use cases, three self-assembling systems of increasing complexity and with existing experimentally quantified pK a changes or pH-dependent phase changes were investigated.…”
mentioning
confidence: 99%
“…23,24 Previous studies that report on IBPs in pH 13 solution found that the alkaline environment disrupted the proteins ability to prevent ice crystal growth, such as a previous study by the authors that demonstrated an IBP from the Antarctic bacterium Marinomonas primoryensis increased grain size in pH 13 solution. 52 As the ice inhibition activity imparted by pThr and 45 kDa pHPMA is not reliant on secondary structure like IBPs, they offer a distinct advantage at preventing ice growth in non-physiological environments compared to their biological counterparts. A previous study performed by Burkey et al 37 investigated the performance of PVA with a molecular weight of 27 kDa at 1 mg/mL in pH 13 solution and found that the reduction in crystal size was ~80%, further corroborating that synthetics perform better in non-physiological environments than IBPs, offering potential ice inhibition strategies in engineering applications, such as freeze-thaw mitigation in cement and concrete in which the pore solution pH is ≥ 13.…”
Section: Resultsmentioning
confidence: 99%
“…23,24 Previous studies that report on IBPs in pH 13 solution found that the alkaline environment disrupted the proteins ability to prevent ice crystal growth, such as a previous study by the authors that demonstrated an IBP from the Antarctic bacterium Marinomonas primoryensis increased grain size in pH 13 solution. 52 As the ice inhibition activity imparted by pThr and 45 kDa pHPMA is not reliant on secondary structure like IBPs, they offer a distinct advantage at preventing ice growth in non-physiological environments compared to their biological counterparts. A previous study performed by Burkey et al 37 investigated the performance of PVA with a molecular weight of 27 kDa at 1 mg/mL in pH 13 solution and found that the reduction in crystal size was ~80%, further corroborating that synthetics perform better in non-physiological environments than IBPs, offering potential ice inhibition strategies in engineering applications, such as freeze-thaw mitigation in cement and concrete in which the pore solution pH is ≥ 13.…”
Section: Resultsmentioning
confidence: 99%